Unacceptable failures: the final report of the Lancet Commission into liver disease in the UK. Issue 10219 (18th January 2020) - Williams, Roger; Aithal, Guruprasad; Alexander, Graeme J; Allison, Michael; Armstrong, Iain; Aspinall, Richard; Baker, Alastair; Batterham, Rachel; Brown, Katrina; Burton, Robyn; Cramp, Matthew E; Day, Natalie; et al.
Summary: This final report of the Lancet Commission into liver disease in the UK stresses the continuing increase in burden of liver disease from excess alcohol consumption and obesity, with high levels of hospital admissions which are worsening in deprived areas. Only with comprehensive food and alcohol strategies based on fiscal and regulatory measures (including a minimum unit price for alcohol, the alcohol duty escalator, and an extension of the sugar levy on food content) can the disease burden be curtailed. Following introduction of minimum unit pricing in Scotland, alcohol sales fell by 3%, with the greatest effect on heavy drinkers of low-cost alcohol products. We also discuss the major contribution of obesity and alcohol to the ten most common cancers as well as measures outlined by the departing Chief Medical Officer to combat rising levels of obesity—the highest of any country in the west. Mortality of severely ill patients with liver disease in district general hospitals is unacceptably high, indicating the need to develop a masterplan for improving hospital care. We propose a plan based around specialist hospital centres that are linked to district general hospitals by operational delivery networks. This plan has received strong backing from the British Association for Study of the Liver and British Society of Gastroenterology, but is held up at NHS England. The value of so-called day-case care bundles to reduce high hospital readmission rates with greater care in the community is described, along with examples of locally derived schemes for the early detection of disease and, in particular, schemes to allow general practitioners to refer patients directly for elastography assessment. New funding arrangements for general practitioners will be required if these proposals are to be taken up more widely around the country. Understanding of the harm to health from lifestyle causes among the general population is low, with a poor knowledge of alcohol consumption and dietary guidelines. The Lancet Commission has serious doubts about whether the initiatives described in the Prevention Green Paper, with the onus placed on the individual based on the use of information technology and the latest in behavioural science, will be effective. We call for greater coordination between official and non-official bodies that have highlighted the unacceptable disease burden from liver disease in England in order to present a single, strong voice to the higher echelons of government.